Pengaturan Artificial Intelligence (AI) Dalam Perspektif Hukum Indonesia: Analisis Normatif Atas Tntangan, Implikasi, Dan Model Regulasi Ideal - Hasanuddin, Moh.; Ferika Nurfransiska; Maryuliyanto (Judge : Jurnal Hukum, 2026)
The rapid advancement of Artificial Intelligence (AI) technology presents significant challenges for Indonesia’s legal system, which currently lacks a comprehensive regulatory framework. This study aims to identify normative gaps in AI governance, analyze the legal implications of AI’s autonomous and adaptive nature, and evaluate the effectiveness of existing legal instruments governing the development and application of AI in Indonesia. Furthermore, the study compares global regulatory approaches to provide evaluative insights for shaping a responsive national model. The research employs a normative legal method, focusing on statutory analysis, academic literature, and international regulatory frameworks. The findings reveal that AI regulation in Indonesia remains sectoral and fragmented, scattered across various laws that were not specifically designed to address the complexity of AI technology. Key legal challenges include issues of social justice, algorithmic accountability, and digital sovereignty. This study recommends an integrated regulatory strategy, encompassing the enactment of a national AI law, harmonization with international standards, establishment of an independent supervisory body, and engagement of multisectoral stakeholders. The proposed strategy aims to build a legal ecosystem that is adaptive, inclusive, and globally competitive.